2010
DOI: 10.1056/nejmsr1003547
|View full text |Cite
|
Sign up to set email alerts
|

HPV Vaccination Mandates — Lawmaking amid Political and Scientific Controversy

Abstract: Proponents of compulsory HPV immunization cited the severity of cervical cancer and the efficacy of the vaccine as primary motivations for wanting to ensure that all girls were vaccinated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 10 publications
1
72
0
1
Order By: Relevance
“…A qualitative assessment of state legislators found that they consider acceptability to parents as one factor in determining whether to pursue HPV vaccine requirement laws (15). While editorials in the medical literature and popular media have highlighted potential parental concerns about HPV immunization requirements (16)(17)(18), the acceptability of requirements to parents is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative assessment of state legislators found that they consider acceptability to parents as one factor in determining whether to pursue HPV vaccine requirement laws (15). While editorials in the medical literature and popular media have highlighted potential parental concerns about HPV immunization requirements (16)(17)(18), the acceptability of requirements to parents is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Differences between HPV infection and other vaccine preventable diseases may contribute to resistance to school requirements. 9 HPV vaccines are primarily intended to prevent a genital cancer caused by a sexually transmitted virus. Requirements have been made for other adolescent vaccines in many states.…”
mentioning
confidence: 99%
“…The term "mandates" or "mandatory" vaccination is used in most discussions of vaccination requirements [10,12,16,17,21,22,26]. Bills requiring HPV vaccinations for school entry were coded as mandatory vaccination if the law mentioned "required" or "mandated" vaccination.…”
Section: Methodsmentioning
confidence: 99%